2012
DOI: 10.1038/emboj.2012.226
|View full text |Cite
|
Sign up to set email alerts
|

Cacnb4 directly couples electrical activity to gene expression, a process defective in juvenile epilepsy

Abstract: Calcium current through voltage-gated calcium channels (VGCC) controls gene expression. Here, we describe a novel signalling pathway in which the VGCC Cacnb4 subunit directly couples neuronal excitability to transcription. Electrical activity induces Cacnb4 association to Ppp2r5d, a regulatory subunit of PP2A phosphatase, followed by (i) nuclear translocation of Cacnb4/Ppp2r5d/PP2A, (ii) association with the tyrosine hydroxylase (TH) gene promoter through the nuclear transcription factor thyroid hormone recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 54 publications
6
91
2
Order By: Relevance
“…Moreover, PKA-activated PP2A-B56δ-dependent dephosphorylation of another DARPP-32 phosphorylation site (Ser-97) induces nuclear import -mediating dopamine-dependent epigenetic functions (25) -and lack of nuclear PP2A-B56δ targeting has been associated with juvenile myoclonic epilepsy (30). There is also evidence that PP2A-B56δ regulates both expression (30) and activity (31) of tyrosine hydroxylase, the rate-limiting enzyme in catecholamine synthesis. Which of these candidate substrates will eventually be of pathologic relevance in our ID patients remains to be further determined in appropriate cellular and animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PKA-activated PP2A-B56δ-dependent dephosphorylation of another DARPP-32 phosphorylation site (Ser-97) induces nuclear import -mediating dopamine-dependent epigenetic functions (25) -and lack of nuclear PP2A-B56δ targeting has been associated with juvenile myoclonic epilepsy (30). There is also evidence that PP2A-B56δ regulates both expression (30) and activity (31) of tyrosine hydroxylase, the rate-limiting enzyme in catecholamine synthesis. Which of these candidate substrates will eventually be of pathologic relevance in our ID patients remains to be further determined in appropriate cellular and animal models.…”
Section: Discussionmentioning
confidence: 99%
“…B56δ has several sites for PKA phosphorylation that activate PP2A-B56δ phosphatase activity (24,29). Moreover, PKA-activated PP2A-B56δ-dependent dephosphorylation of another DARPP-32 phosphorylation site (Ser-97) induces nuclear import -mediating dopamine-dependent epigenetic functions (25) -and lack of nuclear PP2A-B56δ targeting has been associated with juvenile myoclonic epilepsy (30). There is also evidence that PP2A-B56δ regulates both expression (30) and activity (31) of tyrosine hydroxylase, the rate-limiting enzyme in catecholamine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…For proof of principle, we investigated ncRNA expression upon changes in calcium channel (Ca V ) activity, which has been implicated in a variety of neurological disorders such as psychiatric disorders (O'Roak et al 2012; CrossDisorder Group of the Psychiatric Genomics Consortium 2013) or Parkinson's disease, respectively (Sulzer and Surmeier 2013). Thereby, we analyzed differential expression of ncRNAs in knockout mouse models for one of the two brain L-type calcium channels (Ca v 1.3) being implicated in Parkinson's disease (Sulzer and Surmeier 2013) and in lethargic mice, which harbor a nonsense mutation in the gene encoding for the auxiliary voltage-dependent Ca 2+ channel β 4 subunit (Cacnb4), previously described as a model for idiopathic epilepsy and ataxia (Burgess et al 1997;Tadmouri et al 2012). In addition, we applied the customized neuroncRNA microarray to a well-characterized triple-transgenic mouse model (3xTG) for Alzheimer's disease (Oddo et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated targeting of b 4 subunits into the nucleus, suggesting a direct function in activity-dependent gene regulation (Colecraft et al, 2002;Hibino et al, 2003;Subramanyam et al, 2009;Tadmouri et al, 2012). Isoform-specific functions of b 4 splice variants were recently observed in neurons (Etemad et al, 2014).…”
mentioning
confidence: 99%